Is fundoplication mandatory in children with neurological impairment undergoing gastrostomy?. (11th October 2021) - Dreznik, Yael; Baazov, Artur; Dvir, Nadav; Seguier‐Lipszyc, Emmanuelle; Zevit, Noam; Nica, Adrianna; Samuk, Inbal; Shamir, Raanan; Dlugi, Elena; Freud, Enrique; Kravarusic, Dragan
Abstract : Aim: Percutaneous endoscopic gastrostomy (PEG) and surgical gastrostomy (SG) are common procedures in children with neurological impairment (NI) with swallowing difficulties. Pulmonary aspirations are a major concern and performing concomitant or delayed fundoplication is still controversial, especially among these patients. The aim of our study was to review our experience with fundoplication performed concomitantly with gastrostomy or later and to evaluate patient outcomes. Methods: This is a retrospective, cohort study including all paediatric patients who underwent SG or PEG with or without Nissen fundoplication at Schneider Children's Medical Center of Israel between the years 2007 and 2018. Patients' clinical and surgical data were recorded and analysed. Results: Between 2007 and 2018, 345 patients underwent SG or PEG. Of these, 89 patients underwent fundoplication. Of the patients who underwent PEG/SG, 158 (45.8%) were neurologically impaired. Most of the patients who underwent fundoplication ( n  = 69, 77.5%) were NI patients ( P  = 0.0001). NI patients with refractory seizures showed almost no improvement in terms of relief of gastro‐oesophageal reflux disease symptoms following fundoplication ( P  = 0.0001) compared to NI patients without refractory seizures. Conclusion: Our findings suggest that in NI patients a concomitant fundoplication is not mandatory and is not efficacious in preventing gastro‐oesophageal reflux disease in patients with refractory seizures.